The issue of hibah, waqf, and property of muallaf under probate and administration act 1959 : the conflict between syari'ah and civil court / Raja Nazrin Raja Musa…[et al.] - Raja Musa, Raja Nazrin; Mohd Zaharom, Siti Zunairah; Fauzi, Mohamad Ammirul Aiman; Sofruddin, Muhammad Safwan (2014)
This research is concerned with the jurisdictional disputes between the civil courts and the syari'ah courts. With changes and development on the issue of hibah, waqf and property of muallaf, this research is focused on the overlapping decision decided by the civil courts, in which it should not have meddle with as the issue pertaining to hibah, waqf and property of muallaf are under syari'ah courts' jurisdiction. Even with the existence of article 121 (1A), which triumphantly states that any matter under syari'ah courts is no longer the matter under the civil courts' jurisdiction, there are still disputes over the matters mentioned above. This research's main objective is to find to a solution where the separation of jurisdictional power will be adhered by the civil courts.